Transformational Leadership of School Principals in Improving Teacher Professionalism - M Nasruddin; Ida Yulia Mega; Maharani Maharani; Hanisa Zahra Al Adawiah; Leni Anggraeni; Meilisa Sajdah; Tri Hariyati; Khairunesa Isa (Universitas Nurul Jadid, 2025)
The purpose of this study is to analyze the transformational leadership of school principals in improving teacher professionalism at SMPN 7 Kotabumi North Lampung. The focus of the research is directed at the ability of school principals to provide motivation, encourage competency development, and build personal relationships and individual coaching to teachers. This research uses a qualitative approach with a case study type. The data source was obtained from two teachers and all homeroom teachers of grades VII, VIII, and IX. Data collection techniques are carried out through interviews, observations, and documentation. Data analysis uses the stages of data reduction, data display, and data verification with the approach of content analysis, discourse analysis, and interpretation analysis. The results of the study show that school principals implement transformational leadership through the provision of motivation and a shared vision, the implementation of academic supervision, support for teacher competency development, and harmonious interpersonal coaching. This leadership has an impact on increasing the discipline, commitment, creativity, and professionalism of teachers in the learning process. The implications of this study show that the transformational leadership of school principals has a strategic role in creating a collaborative work culture and improving the quality of education through the continuous strengthening of teacher professionalism